2020
DOI: 10.1007/s00134-020-06141-z
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pharmacological therapies for ARDS: COVID-19 and beyond

Abstract: ARDS, first described in 1967, is the commonest form of acute severe hypoxemic respiratory failure. Despite considerable advances in our knowledge regarding the pathophysiology of ARDS, insights into the biologic mechanisms of lung injury and repair, and advances in supportive care, particularly ventilatory management, there remains no effective pharmacological therapy for this syndrome. Hospital mortality at 40% remains unacceptably high underlining the need to continue to develop and test therapies for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 113 publications
0
57
0
Order By: Relevance
“…even if COVID-19 ARDS were an atypical subset of ARDS (and it's not clear that this is indeed the case), should this prompt any changes to management? The "vasocentric" pathophysiology demonstrated in this and many other studies suggests a potential role for vascular interventions such as therapeutic anticoagulation [13]; relevant clinical trials are ongoing. An important question is whether the findings of this study suggest any changes in ventilatory management.…”
mentioning
confidence: 66%
“…even if COVID-19 ARDS were an atypical subset of ARDS (and it's not clear that this is indeed the case), should this prompt any changes to management? The "vasocentric" pathophysiology demonstrated in this and many other studies suggests a potential role for vascular interventions such as therapeutic anticoagulation [13]; relevant clinical trials are ongoing. An important question is whether the findings of this study suggest any changes in ventilatory management.…”
mentioning
confidence: 66%
“…Protective mechanical ventilation strategies can lead to further exacerbation of lung injury caused by over-distention and repetitive mechanical stretch stress associated with ventilator-induced lung injury (VILI) [ [12] , [13] , [14] ]. Pharmacological approaches to alleviate ARDS/VILI do not currently exist but may be rapidly emerging [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigational agents including chloroquine/hydroxychloroquine, azithromycin, dexamethasone, darunavir/ritonavir, lopinavir/ritonavir, favipiravir, and remdesivir are used clinically based on early published evidence of clinical efficacy. In addition, a list of potential drug therapies for acute respiratory distress syndrome (ARDS) in COVID-19–infected patients has been intensively reviewed by Horie et al ( 1 ). A recent results reported by Randomised Evaluation of COVID-19 Therapy (RECOVERY) Collaborative group showed that dexamethasone use in patients with COVID-19 infection receiving respiratory support significantly reduced the 28-day mortality ( 2 ).…”
mentioning
confidence: 99%